Optimization of Controlled Water and Nitrogen Fertigation on Greenhouse Culture of Capsicum annuum - Youzhen Xiang; Haiyang Zou; Fucang Zhang; You Wu; Shicheng Yan; Xinyan Zhang; Jianke Tian; Shengcai Qiang; Haidong Wang; Hanmi Zhou (The Scientific World Journal)
This study investigated the effects of different combinations of irrigation and nitrogen levels on the growth of greenhouse sweet peppers, assessing yield, quality, water use efficiency (WUE), and partial factor productivity from applied N (PFPN). By using controlled drip irrigation, the optimal conditions for efficient, large-scale, high-yield, and high quality production of sweet peppers in Northwest China were determined. Using the local conventional irrigation and nitrogen regime as a control (105% ET0, N: 300 kg·hm−2), three alternative irrigation levels were also tested, at 90%, 75%, and 60% ET0. These were combined with nitrogen levels at 100%, as the control, and 75%, 50%, and 25%, resulting in 16 combination treatments. The results show that different supplies of water and nitrogen nutrition had a significant impact on the growth, yield, WUE, PFPN, and quality of fruit. The treatments of W0.90N0.75, W0.90N0.50, W0.75N0.75, and W0.75N0.50 can better maintain the “source-sink” relationship of peppers. They increased the economic yield, WUE, and PFPN. A principal component analysis was performed to evaluate indicators of fruit quality, revealing that the treatment of W0.75N0.50 resulted in the best fruit quality. For greenhouse sweet peppers produced in Northwest China, the combination of W0.90N0.75 resulted in the highest economic yield of 34.85 kg·hm−2. The combination of W0.75N0.75 had the highest WUE of 16.50 kg·m−3. The W0.75N0.50 combination treatment had the highest fruit quality score. For sustainable ecological development and in view of limited water resources in the area, we recommend the W0.75N0.50 combination treatment, since it could obtain the optimal fruit quality, while its economic yield and WUE were 9% and 4% less than the maximum, respectively. This study provides a theoretical basis for the optimal management of water and nitrogen during production of greenhouse sweet peppers in Northwest China.